In-Plane Strength and Stiffness of Cross-Laminated Timber Shear Walls - Md Shahnewaz; Shahria Alam; Thomas Tannert (Buildings, 2018)
The research presented herein investigated the in-plane performance of cross-laminated timber (CLT) shear walls for platform-type buildings under lateral loading. Finite element models of CLT connections (i.e., brackets, hold-downs and self-tapping screws) were developed in OpenSees and calibrated against experimental tests to represent the connections’ hysteresis behaviour under cyclic tension and shear loading. The results were incorporated into models of CLT single and coupled shear walls. The results in terms of peak displacement, peak load and energy dissipation were in good agreement when compared to full-scale shear wall tests. Subsequently, a parametric study of 56 single and 40 coupled CLT shear walls was conducted with varying numbers and types of connectors (wall-to-floor and wall-to-wall) for evaluating their seismic performance. It was found that the strength, stiffness and energy dissipation of the single and coupled CLT shear walls increased with an increase in the number of connectors. Single shear walls with hold-downs and brackets performed better under seismic loading compared to walls with brackets only. Similarly, coupled shear walls with four hold-downs performed better compared to walls with two hold-downs. Finally, ductility of coupled shear walls was found to be 31% higher compared to that of single shear walls. The findings from this research are useful for engineers to efficiently design CLT shear walls in platform-type construction.